A simple and effective technique to guide the ectopic eruption of a first permanent molar: a case report (Revista da Faculdade de Odontologia - UPF, 2016)
Objective: To report the case of a 5-year-old patient diagnosed with ectopic eruption of the lower left first permanent molar that was mesially inclined, initially based on the clinical examination and followed by periapical radiographic examination. Case report: The treatment consisted of the placement and maintenance of an elastic separator for one week between the space of the lower second primary molar and the lower first permanent molar. Subsequently, the elastic separator was removed, allowing the tooth to erupt freely. After 1 week without the elastic separator, the patient returned and the tooth was observed in adequate eruption. Final considerations: The treatment of ectopic eruption was effective, since it repositioned the first permanent molar and allowed its vertical eruption in a short time using a simple technique. Moreover, the early diagnosis of this eruption disorder of permanent molar in mixed dentition is important to avoid more complex treatments and enable normal occlusion development.